Relevansi Fatwa DSN-MUI Nomor 28/DSN-MUI/III/2002 tentang Jual Beli Mata Uang (Al-Sharf) di Era Digital - Muhammad Dedi (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2023)
The digital era affects various national-international economic transactions. Massive technological developments have had a significant impact on the economy, especially buying and selling transactions. In 2002, foreight exchanger transactions were still carried out manually, as technology grew, this resulted in a technical shift in foreight exchanger transactions from manual to digital. This also certainly affects the fatwa of the National Sharia Council which regulates the buying and selling of foreign currencies. The DSN-MUI fatwa No. 28 concerning the sale and purchase of foreign currencies was formed in 2002. At that time, foreign exchange transactions were still carried out conventionally, so with technical changes to transactions, it was possible that the fatwa needed to be updated so that it was in accordance with the context in society. The approach method in this research is normative juridical. The results of the analysis are described qualitatively and written descriptively. This research found that there are at least some content that is no longer relevant in this digital era, it is necessary to re-discuss it so that the fatwa is in accordance with the existing conditions. This research is expected to be able to contribute ideas, add scientific references and considerations in future research.